Influence of environmental constraints and carrier gas velocity on powder concentration and temperature distribution during laser inside additive manufacturing process. (January 2021) - Li, Yanze; Gu, Dongdong; Shi, Xinyu; Dai, Donghua; Ge, Qing; Sun, Yixuan; Li, Shuhui
Graphical abstract: Highlights: Coaxial nozzle with high convergence applied on LIAM was designed. Effect of deposited plane characteristics on powder aggregation was discussed. Effect of processing parameters on powder flow and thermal behavior was discussed. Mechanisms of interaction of powder flow and inner cylinder wall was discovered. Abstract: Cylinder structures strengthened by internal stiffeners are widely applied in high-speed aircraft and spacecraft that are subjected to harsh environments. However, it is severely challenging to fabricate stiffener structures within a cylinder's restricted space via traditional processes. Techniques that allow for the deposition of metallic structures through zones in difficult-to-access positions, e.g., the inner walls of a cylinder, are quite limited. Laser inside additive manufacturing (LIAM) technology is applied to produce components in the inner walls of thin tubes, whose processing environments are restricted due to their small internal space. Nevertheless, the powder motion behavior driven by the feeding gas and LIAM's operating temperature in the restricted space is not evident. A simulation of the LIAM process as a feasible alternative for application in restricted spaces was investigated in the present study. The effects of the spatial constraints and the carrier gas velocity on the powder flow's aggregation and temperature distribution were studied. It was found that the powder flow was distributed in a convergent shape, which could be divided into an annular area, convergence area, and divergence area. With the increase in the carrier gas velocity, the powder flow concentration was found to decrease gradually. The powder utilization rate of LIAM was found to be as high as 60.5%. Moreover, a higher temperature was achieved in the powder flow for the cylinder substrate due to the difference in the geometric structure and the higher reflection of the cylinder substrate to laser intensity.